Cyclopes and giants: ancient mythological figures through an anatomical and palæopathological lens - Galassi, F.M.; Papa, V.; Lambusta, L.; Vaccarezza, Mauro; Varotto, E. (2022)
This paper examines the origin of the myths about giants and cyclopes from the palæontological and palæopathological perspectives, highlighting how much more attention should be devoted to the possibility that a pituitary condition may have indeed played a role in the mythopoietic process.